2020
DOI: 10.1021/acscentsci.0c00129
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic System Demonstrates That Cas9 Longevity Impacts Genome Editing Outcomes

Abstract: Prolonged Cas9 activity can hinder genome engineering as it causes off-target effects, genotoxicity, heterogeneous genome-editing outcomes, immunogenicity, and mosaicism in embryonic editing—issues which could be addressed by controlling the longevity of Cas9. Though some temporal controls of Cas9 activity have been developed, only cumbersome systems exist for modifying the lifetime. Here, we have developed a chemogenetic system that brings Cas9 in proximity to a ubiquitin ligase, enabling rapid ubiquitination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
(92 reference statements)
1
25
0
Order By: Relevance
“… 30 The result suggested that the PROTAC-FCPF-degraded Cas9 FCPF efficiently repressed the biological function of the CRISPR-Cas9 FCPF system in a time-controlled fashion. In agreement with the result reported by Sreekanth et al, 24 the incubation of PROTAC-FCPF (1 μM) for 24 h reduced the off-target effect from 12.1% to 3.56% ( Figure S2H ), implying that Cas9 degraders can reduce the off-target effects of a CRISPR/Cas9 system.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“… 30 The result suggested that the PROTAC-FCPF-degraded Cas9 FCPF efficiently repressed the biological function of the CRISPR-Cas9 FCPF system in a time-controlled fashion. In agreement with the result reported by Sreekanth et al, 24 the incubation of PROTAC-FCPF (1 μM) for 24 h reduced the off-target effect from 12.1% to 3.56% ( Figure S2H ), implying that Cas9 degraders can reduce the off-target effects of a CRISPR/Cas9 system.…”
Section: Resultssupporting
confidence: 92%
“…They demonstrated that the small molecular degrader, dTAG-47, degraded Cas9 carrying two FK506-binding proteins (FKBPs, Cas9 FKBP ) at the N-terminal and loop region at concentrations of 0.1–1 μM in a 24 h treatment, which significantly increased the specificity of the CRISPR-Cas9 system. 24 We evaluated the activity of PROTAC-FCPF for Cas9 FCPF degradation in both 8 and 24 h treatments. We found that 10 μM PROTAC-FCPF robustly degraded the Cas9 FCPF protein ( Figure 2 C and Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because off-target editing is often slower than on-target editing, regulating the expression of Cas9 improves on-target editing while avoiding off-target editing and subsequent genotoxicity. Several research groups have demonstrated that controlling Cas9 expression levels reduces off-target editing [97][98][99][100][101]. Furthermore, the Cre protein can also be fused with DD to achieve inducible control of gene expression [102].…”
Section: Research Toolsmentioning
confidence: 99%